LIBRARY RESEARCH ON IMPLEMENTATION CHALLENGES OF RESPONSIVE CAREGIVING AND PLAY-BASED LEARNING IN MALAYSIAN EARLY CHILDHOOD SETTINGS (TASKA) - LYANASHIKA JUNIE; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This library research investigates the implementation challenges of responsive caregiving and play-based learning in Malaysian childcare centers (TASKA) for infants and toddlers, focusing on alignment with parental aspirations from 2020 to 2025. By reviewing recent studies on holistic pedagogical methods, parental involvement, staff professionalism, and implementation barriers, the study highlights the essential components of quality early education in TASKA: responsive caregiving, play-based learning, qualified educators, and engaged families. The findings identify significant challenges including resource constraints and training gaps, and offer practical recommendations to enhance program quality, thereby supporting developmental outcomes and meeting modern parental expectations.